Distinct Roles of Mitochondrial HIGD1A and HIGD2A in Respiratory Complex and Supercomplex Biogenesis - Alba Timón-Gómez; Joshua Garlich; Rosemary A. Stuart; Cristina Ugalde; Antoni Barrientos (Cell Reports, 2020)
Summary: The mitochondrial respiratory chain enzymes are organized as individual complexes and supercomplexes, whose biogenesis remains to be fully understood. To disclose the role of the human Hypoxia Inducible Gene Domain family proteins HIGD1A and HIGD2A in these processes, we generate and characterize HIGD-knockout (KO) cell lines. We show that HIGD2A controls and coordinates the modular assembly of isolated and supercomplexed complex IV (CIV) by acting on the COX3 assembly module. In contrast, HIGD1A regulates CIII and CIII-containing supercomplex biogenesis by supporting the incorporation of UQCRFS1. HIGD1A also clusters with COX4-1 and COX5A CIV subunits and, when overexpressed, suppresses the CIV biogenesis defect of HIGD2A-KO cells. We conclude that HIGD1A and HIGD2A have both independent and overlapping functions in the biogenesis of respiratory complexes and supercomplexes. Our data illuminate the existence of multiple pathways to assemble these structures by dynamic HIGD-mediated CIV biogenesis, potentially to adapt to changing environmental and nutritional conditions.